Respostas
respondido por:
1
x^2
----- = 12
x-3
------> x^2 = 12 * (x -3 )
------> x^2 = 12x -36 (passando tudo por um lado e igualando a zero)
------> x^2 -12x +36 = 0
resolvendo delta
Δ = B^{2} -4 (a) (c)
Δ = 12^{2} -4 (1)(36)
Δ= 0 (logo as duas raizes serão iguais)
bhaskara
-B + √Δ
------------ = +12
2 * A ------- = resultado é 6
2
-
----- = 12
x-3
------> x^2 = 12 * (x -3 )
------> x^2 = 12x -36 (passando tudo por um lado e igualando a zero)
------> x^2 -12x +36 = 0
resolvendo delta
Δ = B^{2} -4 (a) (c)
Δ = 12^{2} -4 (1)(36)
Δ= 0 (logo as duas raizes serão iguais)
bhaskara
-B + √Δ
------------ = +12
2 * A ------- = resultado é 6
2
-
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás